Analisis Pembelajaran Berpendekatan Etnomatematika pada Materi Geometri - Mahayani, Krishna; Suparmi, Made; Popsiani, Luh Gede Rossy; Paramitha, Ni Kadek Dwi; Adipranata, Komang Yogi; Werang, Basillius Redan (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
Numeracy problems at SD Negeri 4 Penarukan, Buleleng have decreased in geometry material. The results of ANBK that have been carried out show that numeracy literacy in several indicators such as basic concepts related to geometry and statistics, and solving simple routine math problems has decreased. This study aims to describe the results of a study of learning strategies with an Ethnomathematics approach to improve numeracy literacy in geometry material. The method used in this research is qualitative library research and field study by collecting several relevant articles that discuss the use of the Ethnomathematics approach in the learning process and adjusted to the results of literacy and numeracy of teachers in the field. The results of this study are in the form of a review of five relevant studies related to the ethnomathematics approach to improve numeracy literacy in geometry material and student numeracy literacy. The use of this Ethnomathematics approach should be a solution for schools to improve student learning outcomes and numeracy literacy skills.